Use of a new proximity assay (NanoBRET) to investigate the ligand binding characteristics of three fluorescent ligands to the human β1-adrenoceptor expressed in HEK-293 cells - Soave, Mark; Stoddart, Leigh A.; Brown, Alastair; Woolard, Jeanette; Hill, Stephen J. (Wiley, 2016)
Previous research has indicated that allosteric interactions across the dimer interface of β1-adrenoceptors may be responsible for a secondary low affinity binding conformation. Here we have investigated the potential for probe dependence, in the determination of antagonist pKi values at the human β1-adenoceptor, which may result from such allosterism interactions. Three fluorescent β1-adrenoceptor ligands were used to investigate this using bioluminescence energy transfer (BRET) between the receptor-bound fluorescent ligand and the N-terminal NanoLuc tag of a human β1-adrenoceptor expressed in HEK 293 cells (NanoBRET). This proximity assay showed high affinity specific binding to the NanoLuc-β1-adrenoceptor with each of the three fluorescent ligands yielding KD values of 87.1 ± 10nM (n=8), 38.1 ± 12nM (n=7), 13.4 ± 2nM (n=14) for propranolol-Peg8-BY630, propranolol-3(Ala-Ala)-BY630 and CGP-12177- TMR respectively. Parallel radioligand-binding studies with 3H-CGP12177 and TIRF microscopy, to monitor NanoLuc bioluminescence, confirmed a high cell surface expression of the NanoLuc- 31-adrenoceptor in HEK 293 cells (circa 1500 fmol.mg protein-1). Following a 1h incubation with fluorescent ligands and β1-adrenoceptor competing antagonists, there were significant differences (p < 0.001) in the pKi values obtained for CGP20712a and CGP 12177 with the different fluorescent ligands and 3H-CGP 12177. However, increasing the incubation time to 2h removed these significant differences. The data obtained show that the NanoBRET assay can be applied successfully to study ligand-receptor interactions at the human β1-adrenoceptor. However, the study also emphasizes the importance of ensuring that both the fluorescent and competing ligands are in true equilibrium before interpretations regarding probe dependence can be made.